Enhancing Two Phase-Commit Protocol for Replicated State Machines - Uyanik, Halit; Ovatman, Tolga (IEEE, 2020)
Two-Phase commit (2PC) is a distributed algorithm where a process which wishes to make a commit on a service first needs to make sure that the participating peers are ready for the commit operation. In our study we enhance 2PC for replicated state machine environments by early aborting the state executions of a state machine in case a higher priority state machine checks to commit a value to be written. By applying our approach, when the number of replicas goes beyond 3 our approach wastes significantly less state executions compared to classical 2PC.